Reformulasi Hukum Terkait Batas Usia Maksimal Anak Dalam Pemidanaan Anak - M, Mulyadi; Adfari, Tsabitah Rahmah; Abdullah, Nayla Putri; Yadilla, Natasya; Amelia, Sabina Putri; Wicaksana, Dika Hikmah; Widiastiwi, Alisha Reva; Camilla, Garneta Rizka (Media Hukum Indonesia (MHI), 2024)
As a legal country, of course, Indonesia has all the rules that regulate social life. Every violation committed by society will definitely have legal consequences. However, there are several circumstances that make it possible to receive pardon in legal consequences, one of which is if the perpetrator is still a minor. In Indonesia itself there are three age groups for perpetrators, namely under 12 years, between 12 and 14 years, and between 14 and 18 years. 18 years of age is considered the maximum age limit for child punishment. However, in reality, many children aged 16-18 years commit crimes and even take their lives. Even 18 years old should not be included in the child category, because they are considered to have entered the adult process where they are able to judge what is good and bad. This research aims to see whether the maximum limit for punishing children, namely 18 years of age, is still ideal for use in Indonesia today. The research methodology used in this research is a normative juridical approach. As for the results of this research, we found the urgency of reformulation regarding the maximum age limit for children in child punishment and there are also several views regarding the reformulation of this child age limit.